2017
DOI: 10.1371/journal.pone.0179830
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary inclusion of high concentrations of crude glycerin on meat quality and fatty acid profile of feedlot fed Nellore bulls

Abstract: Crude glycerin, the main by-product of biodiesel production, can replace dietary energy sources, such as corn. The objective of this study was to evaluate the inclusion of up to 30% of crude glycerin in dry matter (DM) of the total diets, and its effects on meat quality parameters of feedlot Nellore bulls. Thirty animals (227.7 ± 23.8 kg body weight; 18 months old) were housed in individual pens and fed 5 experimental diets, containing 0, 7.5, 15, 22.5 or 30% crude glycerin (DM basis). After 103 d (21 d adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The increased level of safflower seeds in the diets did not influence the chemical composition of the Longissimus muscle of lambs (Table 8). The chemical characteristics of the meat aim to carry updated and reliable nutritional information of the final product, showing what consumers will consume (Van Cleef et al, 2017). Therefore, changes in the nutritional values of meat may be undesirable to the consumer.…”
Section: Resultsmentioning
confidence: 99%
“…The increased level of safflower seeds in the diets did not influence the chemical composition of the Longissimus muscle of lambs (Table 8). The chemical characteristics of the meat aim to carry updated and reliable nutritional information of the final product, showing what consumers will consume (Van Cleef et al, 2017). Therefore, changes in the nutritional values of meat may be undesirable to the consumer.…”
Section: Resultsmentioning
confidence: 99%
“…The laboratory material and the material used in the fish capture and transportation were previously sterilized along as well as the media for the solutions. All the required sanitation care was taken tion of human diets calculated based on the nutritional contribution of foods (Gonçalves, Almeida & Borges, 2003;Van Cleef et al, 2017). Fish meat presents high quality protein rich in essential amino acids, complex B vitamins and minerals (such as phosphorus, magnesium, iron and zinc) (Goes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of significant difference in propionic acid concentrations, the combination crude glycerine with essential oil promoted an increase of 17% in this acid, fact that decreased the C2: C3 ratio in the rumen. Although there are also evidence that crude glycerine may have a detrimental effect on the growth of structural carbohydrate fermenting bacteria (AbuGhazaleh, Abo El‐Nor, & Ibrahim, ; Roger, Fonty, Andre, & Gouet, ), resulting in reduced fibre digestibility and CH 4 production (van Cleef et al, ; Homem Junior et al, ; Paschoaloto et al, ), crude glycerine does not impair the consumption, performance or carcass characteristics of feedlot cattle (van Cleef et al, ) and, when combined with essential oil, has shown even better results (Cruz et al, ; Prado et al, ; Silva et al, ; Valero, Prado, et al, ; Valero, Torrecilhas, et al, ).…”
Section: Discussionmentioning
confidence: 99%